2020
DOI: 10.1002/ijc.32903
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 germline testing in Cretan isolates reveals novel and strong founder effects

Abstract: Germline BRCA1 and BRCA2 loss-of-function variants have been linked to increased breast and ovarian cancer risk, with more than 5,000 distinct pathogenic variants being reported worldwide. Among individuals of Greek descent, the BRCA1/2 variant spectrum is heterogeneous, but characterized by strong founder effects. As patients from certain geographical regions of Greece (like Crete) were underrepresented in previous studies, we hypothesized that isolated Cretans, a southern Greece islanders' population with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A limitation of this study involves the selection of variants, which is based on a national database, i.e., CanVaS, which includes genomic data from Greek individuals only. As previously reported, the Greek population is influenced by strong founder effects, and therefore, many of the variants tested can be population-specific [ 36 , 37 , 38 , 39 ]. Although the variant classification per se described herein might not be applicable to genetic data deriving from multi-ethnic cohorts, the approach to automatically classify variants with unknown significance can find broad application.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of this study involves the selection of variants, which is based on a national database, i.e., CanVaS, which includes genomic data from Greek individuals only. As previously reported, the Greek population is influenced by strong founder effects, and therefore, many of the variants tested can be population-specific [ 36 , 37 , 38 , 39 ]. Although the variant classification per se described herein might not be applicable to genetic data deriving from multi-ethnic cohorts, the approach to automatically classify variants with unknown significance can find broad application.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this approach empowers subpopulation analysis, the study of Greek population isolates, and the investigation of possible founder effects. The strong founder effect observed in Greek subpopulations has been recently highlighted in a genetic analysis performed in Cretan isolates, where it was shown that three pathogenic variants in BRCA1 and BRCA2 , unique to the Cretan subpopulation, namely NM_007294.3:c.5492del in BRCA1 and NM_000059.3:c.7806‐2A>T and NM_000059.3:c.6842‐2675_7008‐5558del, both in BRCA2 , account for 48% of identified PVs in BRCA1 and BRCA2 among breast and ovarian cancer patients of Cretan descent (Apostolou et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To provide a first paradigm tackling the aforementioned open challenges, we established CanVaS, a national database that records germline genetic variation and associated clinical data of Greek cancer patients. With CanVaS, we manage to document the genetic heterogeneity of cancer susceptibility genes in Greeks, a population of unique genetic makeup, exhibiting not only extended genetic heterogeneity but also strong founder effects (Apostolou et al, 2017, 2020; Konstantopoulou et al, 2014; Pertesi et al, 2011). Most importantly, all the genetic data are accompanied by detailed phenotypic and clinical traits of tested individuals, whether a pathogenic variant has been identified or not, enabling genotype‐phenotype correlation analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Blood samples were collected from each participant for germline DNA testing when the patients were referred to a Genetic Counseling Unit. All participants were screened for BRCA1 and BRCA2 mutations, either by Sanger sequencing using Applied Biosystems’ 3130XL Genetic Analyzer (Thermo Fisher Scientific, Carlsbad, CA, USA) or by massive parallel sequencing using the TruSight Cancer panel (Illumina, San Diego, CA, USA) on a MiSeq Analyzer, as previously described [ 40 ]. Carriers of variants of uncertain/unknown significance (VUSs) were deemed as non-carriers.…”
Section: Methodsmentioning
confidence: 99%